Marketing Planning, Pricing strategies, and The Use of Online Social Networks for Marketing in A SME - Bruno, Andrea (2013)
The objectives of this dissertation are threefold. The dissertation is firstly aimed at recommending a practically useful marketing plan for Betterlanguages, a Nottingham based SME operating in the language services market. The recommendations for the internal and external analysis of the company are based on the academic tools outlined in the literature review. Second, the dissertation aims at offering suggestions concerning pricing strategy for Betterlanguages, by exploring the pricing literature and researching competitor’s pricing strategies. Third, the dissertation will offer practical recommendations to Betterlanguages to improve its social networking pages, basing those advice on empirical research and on the material reviewed in the literature.